Humor and Satire in Isabelo de los Reyes’s El Diablo en Filipinas - Testa-De Ocampo, Anna Melinda (BANWAAN: The Philippine Journal of Folklore; 2025: Banwaan: The Philippine Journal of Folklore, 2025)
This paper is a preliminary study on humor and satire in Isabelo de los Reyes’s text, Ang Diablo sa Filipinas ayon sa nasasabi sa mga casulatan luma sa Kastila (The Devil in the Philippines according to Ancient Spanish Documents), published in 1886 as a serialized text in La Oceania Española (De los Reyes, 1886/2014). In Isabelo De los Reyes’s efforts to critique the excesses of Spanish rule, he used satire to elicit awareness and laughter, and at the same time, contribute to the creation of an imagined community. The search for the magical librito in a dead man's library is the beginning of a journey of the book as a material object and the exploration of other Spanish historical texts in the library. Unlike Marcelo H. del Pilar's satirical technique of rewriting the Spanish original material in his critique of the excesses of the friars, De los Reyes quotes verbatim (at times in an edited form) from Spanish historical writings. Sharing jokes and laughter towards the Spaniards creates a shared community, increases one’s awareness of abuse, and elicits revolutionary action. Keywords: satire, humor, el diablo, librito, De los Reyes, Gaspar de San Augustin